KAJIAN KUALITAS TERHADAP BUKU MATERI POKOK PENGETAHUAN BAHAN PANGAN HEWANI - UNIVERSITAS TERBUKA - Trimurti Artama; Anang Suhardianto; Welli Yuliatmoko (LPPM Universitas Terbuka, 2009)
This study is to reveal accuracy, recency, legibility,language, and physical appearance the main course material on Animal Food Substance(PANG 4221) by expert perception, lecturers, and students. The result of this study is expected to provide some useful recommendation for the revision of the course material of the Open University (UT). The data were obtained by capturing information from students of UT and non UT. The data obtained were analyzed by using descriptive qualitative methods. In addition, evaluation of the course material delevoped was conducted following the PAU-PPI format. The results the course material has high accuracy, legibility, language, materials, format, print, finishing and binding (score 3-4). However, despite high scores every aspect still needs to be revised because of some in consistencies. The recency, cover design, and content design have the lowest scores (2-3). These aspects must absolutely be revised. It can be concluded that the course material should be revised to include all findings from this study.